Proof of the Existence of Speculative Equilibria - Matthew O. Jackson (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1992)
The existence of speculative equilibria is proven in a simple overlapping generations, infinite horizon economy. In equilibrium, all agents bid assets according to increasing functions of private information which is uncorrelated with the fundamental value (dividend stream) of the asset. This is a unique best response to the strategies of the other agents, which implies that speculative information is valuable.
Keywords: 330